Metagenomic analysis of soil microbial community under PFOA and PFOS stress - Cai, Yanping; Chen, Huilun; Yuan, Rongfang; Wang, Fei; Chen, Zhongbing; Zhou, Beihai (Environmental research. Section A, 2020)
Perfluorinated compounds (PFCs) contamination of soil has attracted global attention in recent years but influences of PFCs on microorganisms in the soil environment have not been fully described. In this study, the effects of perfluorooctane sulphonate (PFOS) and perfluoroctanoic acid (PFOA) on bacterial communities were determined by Illumina Miseq sequencing and Illumina Hiseq Xten. The stimulation of PFCs pollutants on soil bacterial richness and community diversity were observed. Sequencing information indicated that Proteobacteria, Acidobacteria, Actinobacteria, Chloroflexi, Firmicutes, and Gemmatimonadetes were the dominant bacterial phyla. Two genera, Bacillus and Sphingomonas, exhibited adverse responses toward PFCs pollution. Carbohydrate-active enzymes (CAZy), Kyoto Encyclopedia of Genes and Genomes (KEGG) and NCBI databases were used to elucidate the proteins and function action of soil microbial to PFCs pollution. Pathways such as Carbohydrate metabolism, Global and overview maps and Membrane transport in the soil microbes were affected by PFCs stress. CAZy analysis revealed that glycosyl transferases (GTs) in PFCs-polluted soils showed more active, while glycoside hydrolases (GHs) were inhibited severely.
Keywords: půda; mikrobiota; Fluorocarbons; Soil Pollutants; půdní mikrobiologie; Alkanesulfonic Acids; Soil Microbiology; látky znečišťující půdu; kyseliny alkansulfonové; Soil; fluorokarbony; Microbiota